ANALISIS PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE)(Studi Empiris Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Dwi Siyamsih (Pt. Anagata Sembagi Education, 2024)
The aim of this research is to determine the influence of corporate governance, profitability and capital intensity both partially and simultaneously on tax avoidance. This type of research is quantitative research, and the research object is mining sector companies listed on the Indonesia Stock Exchange for the 2012-2016 period. The sample in this research consisted of 11 companies by testing the hypothesis through the classical assumption test, t test, and f test. The results of this research state that corporate governance, which is proxied by the audit committee and audit quality and capital intensity, partially has no effect on tax avoidance, while partial profitability has a significant effect on tax avoidance. Corporate governance as proxied by the audit committee and audit quality, profitability and capital intensity simultaneously have a significant effect on tax avoidance.